城郊经济增长因素分析 = Analysis on growth factors to suburb economy - 张冰水 Zhang, Bingshui (2008)
This dissertation puts forward some suggestions for suburb economy as well, such as to keep going to develop township enterprises, relying on intensive economic growth method, and further developing high-added value and high science & technology products, continuing to push the process of agricultural industrialization, and developing suburb agriculture so as to realize transformation from traditional to up to date & leisure agriculture.